Oral Administration of Influenza Vaccine in Combination with the Adjuvants LT-K63 and LT-R72 Induces Potent Immune Responses Comparable to or Stronger than Traditional Intramuscular Immunization - Barackman, John D. (American Society for Microbiology, 2001)
Mucosal immunization strategies are actively being pursued in the hopes of improving the efficacy of vaccines against the influenza virus. Our group investigated the oral immunization of mice via intragastric gavage with influenza hemagglutinin (HA) combined with mutant Escherichia coli heat-labile enterotoxins K63 (LT-K63) and R72 (LT-R72). These oral immunizations resulted in potent serum antibody and HA inhibition titers, in some cases stronger than those obtained with traditional intramuscular administration, in addition to HA-specific immunoglobulin A in the saliva and nasal secretions. This study demonstrates that it may be possible to develop effective oral influenza vaccines.